PENGARUH SERVICE RECOVERY TERHADAP KEPUASAN PENUMPANG DIBANDARA HUSEIN SASTRANEGARA - Siswhara, Gita; Abdullah, Taufik; Karina, Fauzia Dwisti (THE Journal : Tourism and Hospitality Essentials Journal, 2016)
Tourism is one of industries that is growing quite rapidly and cannot be separated from the roles of other sectors. One of those sectors is transportation. Air transportation service, as the most important transportation, needs assistance from airport that has one of tourism elements which is accessibility. One of the airports in Indonesia, which is Husein Sastranegara Bandung airport, always faces increase in the number of passengers in every year which cause over capacity. It makes PT Angkasa Pura II, as the maintainer of the airport, receive many complaints from the passengers. Those complaints will affect the passengers’ satisfaction. In order to decrease service failure, the airport management applies service recovery in the form of actions, efforts, or process to increase passengers satisfaction. In this study, service recovery that consists of procedural justice, interactive justice and outcome justice. In the other hand, passengers satisfaction which is obtained from the comparison result between the performance perceived by the passengers (perceived) and the passengers’ expectation (expected).The population of respondents in this study is 100 passengers who have ever made complaints and received service recovery at Husein Sastranegara airport. The method used in this study is descriptive- explanatory method with less than a year length of research (cross sectional method). The data analysis and hypothesis test technique used in this study is multiple linear regression. The purposes of this study are to gain and/or get the result about passengers satisfaction towards service recovery. The result of this study shows that the entire dimension of service recovery has significant influence towards passengers satisfaction.